Effect of Dietary Supplement Yeast Culture on Production Performance and Hematological Parameters in Broiler Chicks - Saied , J.M.; Al-Jabary, Q.H.; Thalij, K.M. (International Journal of Poultry Science, 2011)
Twenty-one-day-old commercial broilers chicks (Ross) were used in completely randomized design to evaluate the efficacy of Saccharomyces cerevisiae (SC), grown at 3% Wheat Bran (WB) used solid state fermentation process to produce Yeast Culture (YC), on growth performance and hematological parameters. The YC production test revealed that the fermentation of WB significantly (p<0.05) increased the crude protein and decreased the crude fiber percentage. At 42 d of age birds supplemented with YC consumed more and grew faster and the better gain weight and Caracas weight than broilers given feed without YC. However, no effects observed in decreasing feed conversion ratio. Measurements of the birds blood parameters should that inclusion YC in the diet significantly increased the total protein, albumin, glucose and uric acid while decreased cholesterol and triglyceride concentration. Furthermore, the total WBC and lymphocytes counts were significantly (p<0.05) reduced, but did not effects on the hematocrit and hemoglobin concentrations when compared with the birds of control group. Also there was not significantly effecting on enzymes activity in blood serum of birds received YC. Overall, the maximum responses an achieved when the birds fed with T4 and T5, compared with the other treatments.